Prediction of Citizens’ Decisions on Transport Mode Choice in Bandung City, Indonesia by Using General Linear Model Given existing Level of Pedestrian Friendly Environment - Ariva Sugandi Permana; Ahmad Nazri Muhamad Ludin; Ranjith - Perera (Chemical Engineering Diponegoro University, 2014)
Significant contribution of non-motorized transport to energy and environment has changed the view of people on walking or cycling as one of transport modes. While promoting mass rapid transport, modern cities tend to promote pedestrianization as well to encourage people to walk instead of relying on motorized transport. Creating pedestrian friendly environment in particular parts of the city, especially in CBD, is one such attempt. This study tries to investigate the correlation between perceptions of the citizens on pedestrian friendly environment (PFE) and their decision on the choices of transport modes. The central business district of Bandung City in Indonesia was chosen as the study area. A questionnaire-based research was used to acquire data on citizens’ perception. Eight variables were employed to understand citizens’ perception on PFE. The result shows that PFE does influence citizens’ decision on their transport modes choice.